PEMBUATAN GAME ARCADE “SAVE OUR PLANET” BERBASIS ANDROID - Medisha Araz; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
“Save Our Planet” is an arcade game that has a campaign theme. This game is Android based and has a minimum API Level of Android 4.4 ‘Kit Kat’ (API Level 19). This game is developed Unity 2019.3.15f1 with C# as the programming language. This game has six mini games and each of them provides information to remind the importance of preserving the environment. When a player gets a score that is higher than fifteen, the player could unlock the next mini game and received a tree that will be displayed on the main menu. They could also see the advantages of different trees on the information menu. Based on the results of the beta testing,“Save Our Planet” has already succeeded in providing information about the importance of preserving the environment.